Existence and Uniqueness Theorem for Stochastic Differential Equations with Self-Exciting Switching - Guixin Hu; Ke Wang (Discrete Dynamics in Nature and Society)
We introduce a new kind of equation, stochastic differential equations with self-exciting switching. Firstly, we give some preliminaries for this kind of equation, and then, we get the main results of our paper; that is, we gave the sufficient condition which can guarantee the existence and uniqueness of the solution.